2022
DOI: 10.3390/jfmk7030053
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive and Dual-Task Training: The Key of Stroke Rehabilitation, A Systematic Review

Abstract: This systematic review aims to reveal the effectiveness of proprioceptive exercise combined with dual-task training in stroke patients. The research was conducted using PubMed, Cochrane Library, Web of Science, and Scopus databases to evaluate studies of rehabilitation interventions with proprioceptive and dual-task exercises in patients with stroke. The keywords for the search were: “stroke” AND “proprioception” OR “proprioceptive” AND “rehabilitation” OR “training” OR “exercises” AND “dual-task” OR “task-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…A previous study has confirmed the positive effects of rehabilitation, osteopathy and acupuncture on constipation and pain in patients with cancer (Chiaramonte, Bonfiglio, et al, 2023). Moreover, motor rehabilitation is beneficial to improve intestinal movement (Chiaramonte et al, 2022). Encouraging healthy lifestyles, dietary strategies such as fiber supplements, and increasing water intake may improve constipation in elderly hospitalized patients with intracerebral hemorrhage (Chiaramonte, Bonfiglio, et al, 2023; Deb et al, 2020; Emmanuel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has confirmed the positive effects of rehabilitation, osteopathy and acupuncture on constipation and pain in patients with cancer (Chiaramonte, Bonfiglio, et al, 2023). Moreover, motor rehabilitation is beneficial to improve intestinal movement (Chiaramonte et al, 2022). Encouraging healthy lifestyles, dietary strategies such as fiber supplements, and increasing water intake may improve constipation in elderly hospitalized patients with intracerebral hemorrhage (Chiaramonte, Bonfiglio, et al, 2023; Deb et al, 2020; Emmanuel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“… Faraza et al (2021) observed that improved cognitive ability after a 4-week neuropsychological training could be attributed to higher functional connectivity within the DLPFC. Such evidence provides a basis for the argument that task training, including both ST and DT training, can be used for promoting DT performance ( De Freitas et al, 2020 ; Chiaramonte et al, 2022 ). However, only few reviews discussed its effects in old participants ( Gallou-Guyot et al, 2020 ; Khan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dual-task exercise program that combines cognitive training and physical activity programs for older adults with mild cognitive impairment has been reported [ 19 ]. Recent studies have also reported that dual-task training improved balance and gait function in patients with stroke [ 20 ] and spatio-temporal parameters of gait in older women with dementia [ 21 ]. A previous study has reported that exercises that include dual-task could be the key of therapeutic success to slow down the progression of dementia, but risk of falls during dual task performance compared to single task performance was presented in patients with dementia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%